I need help with these two equations

QUESTION POSTED AT 01/06/2020 - 03:04 PM

Answered by admin AT 01/06/2020 - 03:04 PM

for these you need to rearrange the equations and do substitutions.

 #3 = if x+y=5 then you know x = 5-y

 now substitute that equation for x in the 2nd one so x + 2y = 8 becomes

5-y + 2y = 8 2y - y becomes 1y which becomes y then subtract 5 from each side to get y =3

now replace y with 3 in the first equation x = 5-3 so x = 2 

 so (2,3) is the answer


 same type of work for #4

2x-y=6 ,S0 y = 2X+6

 so now you have 4x+2(2x+6)=-4

that becomes 4x +4x+12 = -4

8x+8 = 1, x =1

y = 2(1)-6 = -4

 so answer is (1,-4)

Post your answer

Related questions

How do you factor the second equation?

QUESTION POSTED AT 02/06/2020 - 01:31 AM

Is (1,-4) a solution to the equation y=-2x

QUESTION POSTED AT 01/06/2020 - 05:03 PM

What is the equation?

QUESTION POSTED AT 01/06/2020 - 04:42 PM